Вплив генної корекції на структуру нирок при експериментальному атеросклерозі - Піскун, Р.П.; Ромашкіна, О.А. (Таврический медико-биологический вестник, 2013)
Изучалась гистологическая структура почек белых лабораторних крыс-самцов репродуктивного возраста в условиях експериментального атеросклероза и его коррекции геном аполипопротеина-Е. Выявлены патологические изменения в строении частей нефрона смоделированной патологии и тенденция к нормализации структуры всех элементов при генной коррекции. The histological structure of male adult laboratory rats’ kidneys has been studied under condition of experimental atherosclerosis and correction of it with the help of apolipoprotein-E. We have analyzed the pathological changes in the structure of nephrons elements in the modelled pathology and the tendency to normalization of the structures of all the elements at application of gene correction.